The Literary Roots of Southern Westerns - Lauric Guillaud (Revue LISA)
This article traces the literary sources of the Western movie genre in the Gothic, a predominantly Southern mode, and in 17th and 18th century American Southern literature. The moving geography of the United States, which expanded West with the gradual settlement of the Frontier, turned such border states as Kentucky the West and the South into places of encounter for the Western and the Southern. The Western genre often borrowed from Southern codes and tropes – for instance violence, individualism, and honor. Landscapes, notably Monument Valley in the Western, and the swamp in the Southern, point towards the American obsession for the dichotomy between civilization and the wilderness – a dichotomy which transcends the Frontier West.